English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

{5x-2y=4
{3x+y=9

{5x-2y=4
{-2(3x+y=9)

{5x-2y=4
{-6x-2y=-18
+________
-x = -14
Wel... by then I realize its wrong.... The answer is supposed to be (2,3) but i dont see what I can be doing wrong, Plz show me I dont wanna get stuck and desperate like the last two nights....

2007-07-18 13:22:05 · 10 answers · asked by Poseidon 2 in Science & Mathematics Mathematics

10 answers

Subtract the second equation from the first, don't add them. You do this because you want the y terms to cancel out.

So you have this:
{5x-2y=4
{-6x-2y=-18

Now subtract the 2nd equation from the first:
(5x - (-6x)) + (-2y - (-2y)) = 4 - (-18)
11x + 0 = 22
11x = 22

Divide both sides by 11:
x = 2

Now plug 2 back in:
5(2) - 2y = 4
10 - 2y = 4
-2y = -6
y = 3

And plug (2,3) into the other equation to check your answer:
3(2) + (3)
= 6 + 3
= 9
So the answer checks.

2007-07-18 13:26:55 · answer #1 · answered by whitesox09 7 · 0 0

When you multiplied the second equation by -2, and then subtracted it from the top equation to eliminate it, you forgot to change the sign on the -6x and add it to the 5x which would have given you 11x=22, x=2.

5x-2y=4
3x+y=9

5x-2y=4
-2(3x+y=9)

5x-2y=4
-6x-2y=-18

5x-2y=4
-(-6x-2y=-18) when subtracting them, don't forget to change each sign

5x-2y=4
6x+2y=18 now add them together

11x=22
x=2 sub x=2 back into either equation and solve for y

5(2)-2y=4
10-2y=4

2y=6

y=3

2007-07-18 13:35:58 · answer #2 · answered by shilohkid13 1 · 0 0

{5x - 2y = 4
{-6x - 2y = -18
(-)________ ---> This is what you did wrong, not (+) but (-), since you want to eliminate the y
11x = 22
x = 2

{3x + y = 9
3*2 + y = 9
y = 3

2007-07-18 13:32:23 · answer #3 · answered by AL 2 · 0 0

To eliminate a variable, you have to add opposites. You did -2 + -2, which only gives you -4. You need 0, so you need -2 + 2. Multiply the second original equation by 2 then do it. 11x=22, x=2, and do the rest!

2007-07-18 13:27:55 · answer #4 · answered by Geekyweirdboylovaa 2 · 0 0

2-y-2y=-4y

You are canceling them when you should be adding them. If you want to substract them then the rest of the equation changes.

5x-(-6x)=11x

4-(-18)=22

11x=22==>>x=2

2007-07-18 13:37:01 · answer #5 · answered by fefe k 2 · 0 0

Don't multiply by -2, multiply by 2 and add the 2 equations together. then you get 11x =22 or x = 2

2007-07-18 13:27:24 · answer #6 · answered by dr_no4458 4 · 0 0

to eliminate the y's since they are opposing signs just multiply 2nd equation by 2 then add.
to get 11x =22 x=2

2007-07-18 13:34:30 · answer #7 · answered by 037 G 6 · 0 0

you mistake is that you are subtracting if you want to eliminate -2y
so 5x-(-6x)=11x
4-(-18)=22
so x=2
The easier way would be to multiply the second equation by 2 instead of -2, then you can just add.

2007-07-18 13:26:59 · answer #8 · answered by leo 6 · 0 0

5x - 2y = 4
6x + 2y = 18----ADD

11x = 22
x = 2

6 + y = 9
y = 3

2007-07-18 23:25:36 · answer #9 · answered by Como 7 · 0 0

Graphing is my least in demand via fact it particularly is amazingly time ingesting and in the experience that your traces are not appropriate, your component to intersection would be complicated to evaluate. additionally, in graphing, in the experience that your answer is a fragment, then it particularly is complicated to make certain that interior the graph. If the two equations are already set up as to y = some thing or x = some thing, then substitution is way less complicated to apply. as an occasion: y=2x + 8 y=3x-4 then you definately might set it up as 2x+8=3x-4, and remedy for x. in spite of the shown fact that, if the equations are written in known form, it particularly is way less complicated to apply removal. as an occasion: 2x+3y=sixteen 4x-3y=8.

2016-10-21 23:40:37 · answer #10 · answered by frasier 4 · 0 0

fedest.com, questions and answers